A New Approach for Stability Analysis of Discrete Systems. Issue 5 (2nd September 2016) - Gaidhane, Vilas H.; Hote, Yogesh V.
ABSTRACT: In this paper, a new approach is presented to calculate the stability margin of the discrete systems. It is based on the algorithm for reduced conservatism of eigenvalues and the Gerschgorin circle theorem. The necessary and sufficient condition for conservatism of eigenvalues of matrix is stated and proved mathematically. Moreover, the proposed approach is illustrated with an example and it is compared with the other existing methods.